Peran Layanan Bimbingan Kelompok terhadap Attention Getting Behaviors (perilaku mencari perhatian) Kelas XI Otomotif SMK Negeri 1 Kalijambe Tahun Pelajaran 2022/2023 - Shilmanindita, Hafi (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2023)
Abstract: This study aims to determine the role of Group Guidance Services on Attention Getting Behaviors in Class XI Automotive at SMK Negeri 1 Kalijambe in the 2022/2023 academic year.This study uses the Guidance and Counseling Action Research (PTBK) method. It was held at SMK Negeri 1 Kalijambe, Sragen. The subjects in this study were 9 students of class XI. This research was carried out for 3 (three) cycles. Each cycle consists of 4 (four) stages, namely planning, action, observation and reflection. Data collection techniques used in this study were interviews, observation and documentation. Many students have attention seeking behavior with various characteristics. Usually shown with an overacting or excessive attitude such as asking unimportant things, disturbing friends, making noise and other attention seeking behavior at SMK Negeri 1 Kalijambe. This has a negative impact on other people. Based on the results of research on the attention-seeking behavior of class XI Automotive students at SMK Negeri 1 Kalijambe in the 2022/2023 academic year, the percentages in each cycle are as follows: At the Pre-Cycle stage with symptoms in accordance with the characteristics of attention seeking behavior of 55.5%, Cycle I was 40.2%, Cycle II was 18.7%, and Cycle III was 16.6%. This indicates that the Group Guidance Service is effective in dealing with students who have Attention Seeking Behavior. Keywords: Group Guidance Services, Attention Seeking Behavior, PTBK